The Challenges of Using the Omnibus Law Method in Indonesia’s Legal System - Widayati, Widayati; Winanto, Winanto; Laksana, Andri Winjaya; Huda, Moh. Nurul; Fareha, Nur (Faculty of Sharia, Universitas Islam Negeri (UIN) Profesor Kiai Haji Saifuddin Zuhri Purwokerto, Indonesia, 2025)
The introduction of the Omnibus Law with Law Number 11 of 2020 on Job Creation marked a significant change in Indonesia’s approach to legislation, as this method was previously unfamiliar in the country. Consequently, the law faced legal challenges and was brought before the Constitutional Court (MK) for review. The Court ruled that the legislative process was flawed, highlighting a lack of public involvement and transparency, and found that the omnibus law method did not have a solid legal foundation within Indonesia’s existing legal framework. In response to these concerns, the House of Representatives and the President passed Law Number 13 of 2022, which included guidelines for using the omnibus law method in future legislation. This method is widely used in common law countries, while Indonesia operates under a civil law system rooted in democratic principles. This study focused on examining implications of the omnibus law method through a normative juridical approach, utilizing secondary data and qualitative analysis. The findings show that while this method can streamline the drafting and discussion of laws—saving time and effort—it also has significant downsides. This include a tendency to prioritize practicality over thorough research and limited public engagement, which undermines its democratic nature. Therefore, if Indonesia chooses to continue using the omnibus law method, it is crucial to address these limitations. Specifically, there must be genuine opportunities for public participation that go beyond just empty formalities. Careful and accurate implementation is needed to ensure that the resulting legislation is effective, high quality, and ultimately regarded as beneficial by the community.